Pengaruh Penerapan Nilai-Nilai Tri Hita Karana dan Kualitas Pelayanan terhadap Kepuasan Tamu Sanctoo Suites & Villas - Swardika, I Nyoman Adi; Wilyadewi, I Dewa Ayu Yayati (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study was to determine the effect of Tri Hita Karana and service quality on guest satisfaction. This research was conducted at Sanctoo Suites & Villas located in Sukawati District, Gianyar Regency. The population in this study is 6,820 people in 2022 with a sample of 99 people using the Slovin Formula using the accidental sampling method. Data collection was carried out using observation, interviews, documentation, literature, and questionnaires as measured by a Likert scale with five answer choices. The instrument test was carried out by testing the validity and reliability. The analysis technique used is multiple linear regression. The results of the partial significance test show that Tri Hita Karana has a positive and significant effect on guest satisfaction, and service quality has a positive and significant effect on guest satisfaction.